Konsep Distribusi Pendapatan Dalam Islam - Moh. Ah. Subhan ZA (JES (Jurnal Ekonomi Syariah), 2016)
The main problem of social life in the community is about how to make the allocation and distribution of income well. Inequality and poverty basically arise not because of the difference of anyone’s strength and weakness in getting livelihood, but because of inappropriate distribution mechanism. With the result that wealth treasure just turns on the rich wealthy, which is in turn, results in the rich get richer and the poor get poorer.Therefore, a discussion on distribution becomes main focus of theory of Islamic economics. Moreover, the discussion of the distribution is not only related to economic issues, but also social and political aspects. On the other side, the economic vision of Islam gives priority to the guarantee of the fulfillment of a better life. Islam emphasizes distributive justice and encloses, in its system, a program for the redistribution of wealth and prosperity, so that each individual is guaranteed with a respectable and friendly standard of living. Islam recognizes private property rights, but the private property rights must be properly distributed. The personal property is used for self and family livelihood, for investment of the working capital, so that it can provide job opportunities for others, for help of the others through zakat, infaq, and shodaqoh. In this way, the wealth not only rotates on the rich, bringing on gap in social life.The problem of wealth distribution is closely related to the welfare of society. Therefore, the state has a duty to regulate the distribution of income in order that the distribution can be fair and reaches appropriate target. The state could at least attempt it by optimizing the role of BAZ (Badan Amil Zakat) and LAZ (Lembaga Amil Zakat) which has all this time been slack. If BAZ and LAZ can be optimized, author believes that inequality and poverty over time will vanish. This is because the majority of Indonesia's population is Muslim. Keywords: distribution of income, State’ role, Islamic economics